Microfoundations of dynamic managerial capabilities: A personality perspective - TEA, Alan Jiun Haw (Institutional Knowledge at Singapore Management University, 2022)
Research in dynamic capabilities (Teece 2007) looks at how organizations derive and potentially sustain competitive advantage by dynamically making sense of opportunities, marshalling and manipulating assets and resources in response to these opportunities (Eisenhardt & Martin, 2000; Teece, 2007). The study of dynamic managerial capabilities is concerned with the microfoundations – attendant attributes as it were – that underpin managers’ ability to effectively participate in the dynamic capabilities of sensing, seizing and reconfiguring (Helfat & Martin, 2015b; Helfat & Peteraf, 2015). Apart from the predominant cognitive account of microfoundations, there remains an under-theorized and underresearched gap in the field of strategic management on the dispositional attributes of middle managers as potential microfoundations of dynamic managerial capabilities. The personality disposition of extraversion followed by conscientiousness are generally regarded as the two strongest personality predictors of leadership effectiveness and emergence in the organizational psychology literature (T. A. Judge, Bono, et al., 2002; Cogliser, Gardner, Gavin, & Broberg, 2012). This study thus hypothesizes that extraversion would similarly show up as a predictor of the sensing, seizing, and reconfiguring aspects of dynamic managerial capabilities; while conscientiousness, on the other hand, would be negatively related to the sensing and reconfiguring aspects of dynamic managerial capability. The study examines non-public archival data on 323 focal managers from a publicly listed Japanese multinational company, a global leader in its mainstay business segment of industrial materials in the advanced manufacturing industry. The personality disposition of extraversion was found to positively influence managerial performance in the dynamic managerial capabilities of sensing, seizing, and reconfiguring, while that of conscientiousness was found to be negatively related to sensing and reconfiguring. The results on extraversion is not surprising given the behavioral imperative for middle managers to actively scan the internal and external environment for opportunities, engage with multiple stakeholders to develop and deploy strategic initiatives, as well as influence organizational constituents towards a vision for change. The results on conscientiousness raises an interesting conundrum for practitioners and organizations alike seeking to hire and develop the ‘best’ managers, as the very qualities of conscientiousness that support managerial performance in task and operational effectiveness would appear to also inhibit performance in dynamic capabilities, thus signalling that what's best for organizational structure and stability may not be best for strategic adaptability. The research calls to attention the potentially equivocal and complex issues involved in the selection, retention and deployment of managerial human resources, especially in the middle management rung of an organizational hierarchy, as firms undergoing strategic change consider how best to shore-up and preserve the competitive advantage arising from its human capital.